Synthesis and characterization of activated carbon doped titanium dioxide nanoparticles for supercapacitor / Mohd Syafiq Affandi Mohd Rusdi - Mohd Rusdi, Mohd Syafiq Affandi (Faculty Of Applied Sciences, 2018)
AC doped Ti02 nanoparticles were synthesis via ultrasonic assisted sol-gel method which are utilized as supercapacitor materials. The electrochemical properties of the AC/TiO2 nanoparticles were investigate using Cyclic Voltammetry (CV) analysis. The crystal structure of the composite has been characterized by X-ray diffraction analysis (XRD) and Fourier transform infrared spectroscopy (FTIR). The electrochemical measurements reveal that the specific capacitance of 267.910 and 226.190 Fg-1 have been obtained for 20% Ti02 loading at 50 and 100 mVs-1 respectively with good capacity retention, as it maintained 90% of its original capacitance after 100th subsequent cycles. The XRD pattern confirmed the purity of ACrri02 nanoparticles and the crystallite sizes of AC/TiO2 in composites were smaller than the undoped samples. The FTIR analysis reveal that the presence of carbonyl group of AC/TiO2 nanoparticles is advantageous to fast faradaic reactions resulted good capacitance. Therefore, results demonstrated that the AC/TiO2 nanoparticles is a promising electrode material for supercapacitor application.